Inequality and Europe 2020 - Francesco Bogliacino (Intereconomics, 2014)
The European Commission put forward its strategy for the 2010-2020 period in its Europe 2020 Communication. Inequality should be seen as a cornerstone of both sustainable and inclusive growth. In fact, unequal societies are also more unstable societies (i.e. unsustainable) and more polarised (i.e. exclusive). The analysis of available data and the established consensus in the literature shows four main stylised facts.
Keywords: 330; EU-Sozialpolitik; Soziale Ungleichheit; Soziale Integration; EU-Staaten